Developing Children’s Melodic and Rhythmic Skills With Playful Tasks in Classroom Music Lessons - ASZTALOS, Andrea (Studia Universitatis Babes-Bolyai Musica, 2024)
The development of children's musical abilities and skills is a complex process, and educators play a crucial role in guiding this journey. Introducing playful tasks into classroom music lessons is a method that empowers educators to enhance children's rhythmic and metric skills. This paper presents playful tasks, allowing educators to guide children in developing their melodic and rhythmic skills through a variety of fun activities. By using these playful tasks, educators can effectively enhance the development of students' musical skills.